Etika dan Integritas Pejabat Publik: Studi Kasus Pemalsuan Surat Tanah oleh Mantan PJ Walikota Tanjungpinang - Elvia Putri Ayu Anggraini; Alfitri Yusuffaza Khalifda Qrisdadra (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the ethical and integrity dimensions of public office through a normative analysis of land document forgery involving a former Acting Mayor of Tanjungpinang. Employing a library research design, the study synthesizes legal literature in criminal law, administrative law, land law, and public ethics to construct an integrative analytical framework. The findings indicate that land document forgery committed by public officials constitutes not merely an individual criminal act, but a structural ethical failure rooted in the abuse of public authority. The misuse of administrative power amplifies legal harm, undermines legal certainty in land administration, and erodes public trust in governmental institutions. Existing literature further reveals that fragmented enforcement mechanisms and sectoral ethical controls are insufficient to address misconduct involving high-ranking public officials. The study argues that effective prevention of land-related crimes requires the integration of ethical governance, institutional oversight, and legal accountability within public administration. By positioning ethics and integrity as core variables of legal analysis, this research contributes to a broader understanding of land forgery as a systemic governance failure rather than an isolated legal violation.